α-glucosidase inhibitory and antioxidant activities of different ipomoea aquatica cultivars and lc–ms/ms profiling of the active cultivar - Lawal, Umar; Leong, Sze Wei; Shaari, Khozirah; Ismail, Intan Safinar; Khatib, Alfi; Abas, Faridah (2016)
The present study was designed to investigate the effect of Ipomoea aquatica extracted using water and methanol at various concentrations on the total phenolics, antioxidant capacity, and a-glucosidase inhibitory activities. Three I. aquatica cultivars were used in this study including the upland type with narrow leaves (K-11), low-land aquatic types with broader shaped leaves (K-25), and bamboo-shaped leaves (K-88). The results revealed that 70% methanol extract of K-11 showed higher total phenolic content and a-glucosidase inhibitory and antioxidant activities than the other two cultivars. The phytochemical constituents in the active extract K-11 were analyzed by means of liquid chromatography coupled with diode array detection and electrospray tandem mass spectroscopy. Eighteen compounds were detected of which 13 were tentatively identiﬁed as quercetin-3-O-sophoroside, quercetin-3-O-glucoside, quercetin-3,7-di-O-glucoside, nomilinic acid glucoside, 4,5-di-O-caffeoylquinic acid, 3,5-di-O-caffeoylquinic acid, luteolin-7-glucoside and 3,4,5-tricaffeolquinic acid, fatty acid together with quercetin, and tricaffeoylquinic acid derivatives.